The Analysis of Common Mistakes Made by Chinese Department Students of Binus University in Learning Mandarin - Andyni Khosasih (Humaniora, 2012)
Article was presented in two sections, those were general overview of Chinese Department of Binus University and common mistakes made by students in learning Mandarin. To find the data, a direct observation was done in the classrooms. It can be concluded that in learning Mandarin, students’ mistakes are caused by the influence of using the mother tongue, the laziness of students in learning the language, and the lack of basic Mandarin knowledge. Common mistakes made by the students in language skills area are pronouncing vowels and consonants, intonation, grammar, Hanzi characters, and vocabularies.